(untitled) (Cardiovascular Journal, 2020)
Background: Cardiopulmonary bypass is associated with increased incidence of hyperglycemia. Many studies have shown that diabetes is associated with increased morbidity and mortality in coronary artery bypass (CABG) surgery. We reviewed the outcome of on-pump versus off pump CABG in diabetic patients. Methods- 80 Adult diabetic patients undergoing isolated CABG both on-pump and OPCAB were divided into 2 groups – 40 patients in each group. To evaluate both preoperative, perioperative and postoperative out come and to compare their in hospital outcome mortality and morbidity. Results: Diabetic patients undergoing coronary artery bypass grafting without cardiopulmonary bypass had fewer complications, including neurological dysfunction (7.5% vs. 10.0%, p=0.1), and reduced incidence of prolonged ventilation (7.5% vs. 12.5%, p = 0.709), atrial fibrillation (15.0% vs. 20.0%, p = 0.002), and renal dysfunction (10.0% vs. 17.5%, p=0.556). In postoperative period, 70% patients in OPCAB group did not experience any cardiac events whereas 30% patients developed myocardial infarction, 5% had cardiac arrest and 7.5% had low output syndrome. . In on pump group 65% patients had no cardiac events whereas 35% patients developed one or more cardiac events. Of them 20% patients developed atrial fibrillation, 2.5% developed myocardial infarction, 2.5% develop cardiac arrest and 10% had low output syndrome. 2.5% patient developed both atrial fibrillation and low output. Conclusion: Diabetic patients undergoing CABG without cardiopulmonary bypass compared with those having coronary artery bypass grafting with cardiopulmonary bypass had higher mean predicted mortality and morbidity. Cardiovasc. j. 2020; 13(1): 12-18